Epidermoids in the Cerebellopontine Angle Region - Waheed Alam, Haider Ali, Shakir Mahmood, Shafaat Hussain, Sohail Ahmad, Muhammad Mushtaq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim and objectives: To understand the development and outcomes of the treatment of cerebellopontine angle epidermoid. Materials and methods: The prospective study was conducted at the neurosurgery department of Lady Reading Hospital Peshawar from January 2023 to June 2023 after approval from the institutional review board. A total of 86 participants were included in the study through a convenient sampling technique. The age of the participants was from 15-65 years, irrespective of their gender. Individual informed consent was obtained from the participants. All the data was collected from patient’s examinations and lab investigations. The collected data was analyzed by using the latest version of SPSS 24. Results: A total of 86 participants were selected for the current study and their age was from 15-65 years. (25) 29. 06 % and (22) 25.58 % of them were from 26-35 and 56-65 years of age respectively. The mean age of the participants was 39 ± 6.24 years. There were 48.83 % (42) males and 44 (51.16 %) female participants. The mean duration of symptoms was 6.8 ± 2.64 months. . Headache was the most common symptom 72.09 % followed by hearing impairments 25.58 %. 22.09 % of them had 22.09 % vertigo and 20.93 % had tinnitus, furthermore, 31.59 % had an imbalance. 30.23 % and 9.30 % had positive cerebellar signs and pyramidal signs respectively. 73.13 % and 11.94 % retro sigmoidal and retro sigmoidal plus sub-temporal surgical approaches. 29 (43.28 %) had a gross total, and 23 (34.32 %) had a near-total resection of epidermoid. Conclusion: The current study concluded that accurate diagnosis can be made through a proper assessment and investigation of the patients. Furthermore, surgical interventions were safe and effective procedures for patients having CP angle epidermoids depending upon the techniques and post-op care of the patients to minimize the complications after the surgery. Keywords: Cerebellopontine angle, Epidermoid, Trigeminal neuralgia, Cerebellar signs.